Migration Activities, Household Characteristic and Child Health in Indonesia - Muhammad Faisal Akbar; Devi Valeriani (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
This paper investigates the impact of household characteristics on child health outcomes in Indonesia using Indonesian family Life Survey. This paper using birth wage, infant mortality and Z score to represent child health. Using Random effect method and random effect probit method, this paper found sending migrant household have larger amount of infant mortality case than non-sending migrant household. According to that findings we know that sending migrant household dominated by families with low incomes. However, we also find food consumption have influence of child health in the families. These results provide a broader view of the economic characteristics of households and their consequences for infant health than is offered by the existing literature.Keywords: The authors are requested to supply 3-5 Keywords, separated by a comma, that can be used for indexing/abstracting purposes.